ANALISIS GEOMETRIK KERATAAN PADA PRODUK MESIN MILLING CNC PROTOTYPE 3 AXIS - Dailimi, Amad; Oleh, Oleh; Dirja, Iman (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Mechanical and control system capable of reading N, G, F, T, and other code instructions. The codes will be instructed to the CNC machine interface system, so that the machine can work in accordance with the program listings that have been made. In general the selling price of this machine is still very high. Therefore, in this study designed a CNC machine with low cost which is intended for small and medium enterprises (SMEs). This CNC milling assembly machine has 3 axes that is X, Y and Z axis. In this research, the CNC milling 3 axes machine is consists of several important components such as guide ways, transmission system, driver and controller. These components are widely available in the market. CNC milling machine has dimensions size of machine length of 700 mm x width of 600 mm x height of 1227 mm. the CNC milling machine 3 axes has advantages that can make several types of wood carving products and acrylic. The results of the test where obtained accuracy of CNC milling 3 axes machine for Y axis that was 0.1946 mm and for X axis of 0.2463 mm.